Planning and Endograft Related Variables Predisposing to Late Distal Type I Endoleaks. (September 2019) - Mascoli, Chiara; Faggioli, Gianluca; Gallitto, Enrico; Longhi, Matteo; Abualhin, Mohammad; Pini, Rodolfo; Massoni, Claudio B.; Freyrie, Antonio; Stella, Andrea; Gargiulo, Mauro
Abstract : Objective: Late distal type I endoleak (ELIB) hampers the outcome of endovascular repair (EVAR) for abdominal aortic aneurysm (AAA); however, only few dedicated experiences have been reported in the literature. The aim of the study was to evaluate the incidence, presentation and treatment of late ELIB and to identify possible anatomical and technical predictors. Methods: All patients undergoing elective EVAR between 2008 and 2013 were collected prospectively. Follow up was by post-operative computed tomography angiography (CTA) performed within 30 days and CTA and/or duplex ultrasound (DUS) at six or 12 months and yearly thereafter. Patients with late ELIB, defined as distal type I endoleak detected more than six months after the primary intervention without endoleak on the intra-operative completion angiogram and on the post-operative CTA, were retrospectively selected (G1) and compared with a control group with no ELIB (G2) homogeneous for clinical conditions, endograft implanted, and timing of follow up. The minimum follow up required for inclusion in the study was 24 months. Pre-operative morphological aorto-iliac features and EVAR implant details were evaluated, and measurements performed after centre lumen line reconstructions using dedicated software. The differences between G1 and G2 were analysed using the chi-square test, the Student t test, and logistic regression. Results: Six hundred and sixteen patients were submitted to EVAR. ELIB was detected in 14 cases (2.3%) (G1) at a median follow up of 32.8 (IQR 48) months. In three of the 14 cases ELIB was symptomatic (AAA rupture, 2; pain, 1); in the remaining 11 cases it was asymptomatic and found incidentally at routine follow up. Treatment was by open repair in one case and by endovascular iliac leg extension in 13 cases. Hypogastric exclusion was necessary in two of 14 cases. Thirty patients were included in G2, with a median follow up of 41.2 (25) months. Common iliac artery length <4 cm (OR 5.3, 95% CI 1.1–29.5, p  = .05), diameter > 15 mm (OR 3.5, 95% CI 1.2–10.9, p  = .03), and severe thrombotic apposition (>50% of circumference) (OR 5, 95% CI 1.2–19.2, p  = .02), at the iliac sealing zone were significant predictors of ELIB, on univariable analysis; oversizing of the iliac leg diameter < 10% and distal sealing > 1 cm above the hypogastric origin were independently associated with ELIB (OR 5.4, 95% CI 1.3–21.5, p  = .01 and OR 6.6, 95% CI 1.1–39.3, p  = .03, respectively), on multivariable analysis. Conclusion: The present data underline that ELIB is a non-negligible occurrence during long term EVAR follow up and requires further interventions, most often by endovascular solutions. According to the ELIB risk factors identified in this study, an iliac leg diameter oversize >10% and extensive common iliac artery coverage (<1 cm above the hypogastric origin) would be suggested to prevent this complication.